KONDISI VEGETASI DAN POPULASI Raflesia patma Blume DI CAGAR ALAM LEUWEUNG SANCANG (Conditions of Vegetation and Population of Rafflesia patma Blume in Leuweung Sancang Nature Reserve) - Resti Suwartini; Agus Hikmat; A. M. Zuhud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
Rafflesia patma Blume is a holoparasite plant. This species is protected by law due to its rarity. The study of vegetation and population conditions of R.. patma was conducted in Leuweung Sancang Nature Reserve, Garut, West Java. The results indicated that due to human activitie withi the Nature Reserve, the vegetation condition at the habitat of R.. patma was experiencing disturbances and the population of R.. patma tent to decrease.Keywords : Rafflesia patma, holoparasite, rare species, nature reserve, habitat